Association of psoriasis with the VEGF gene polymorphism in the northern Polish population. (19th December 2011) - Zablotna, M.; Sobjanek, M.; Nedoszytko, B.; Lange, M.; Kozicka, D.; Glen, J.; Roszkiewicz, J.
Abstract Background Neovascularization plays an important role in pathogenesis of psoriasis and vascular endothelial growth factor (VEGF) seems to be the main angiogenic factor involved in this disease. Published studies which analysed the role of VEGF gene polymorphism in psoriasis were limited and they received controversial results. Objective The aim of our study was to evaluate the association between −1154 G/A, −460 T/C and +405 G/C polymorphisms and the psoriasis susceptibility and to determine whether this genetic variation influence levels of VEGF protein expression. Materials and methods One hundred and eighty‐nine patients with psoriasis and 215 ethnically matched controls were genotyped using ARMS‐PCR and PCR‐RFLP methods. VEGF serum levels were assessed in 47 patients and 40 controls using ELISA test. Results We noted that an increased risk of Type I psoriasis is associated with −1154 G allele (OR = 1.9; P = 0.04), +405 CC (OR = 2.86; P = 0.03) and −460 TT (OR = 1.56; P = 0.05) genotypes and demonstrated that a significantly increased risk of developing disease is related to presence of haplotype GTC among all patients (OR = 1.97; P = 0.001), patients with Type I (OR = 1.87; P = 0.005) and Type II psoriasis (OR = 2.37, P = 0.01). We have found significantly increased serum levels of VEGF in patients with psoriasis compared with those in healthy controls (P = 0.008). Serum levels of VEGF significantly correlated with PASI: r = 0.72, P < 0.00001. Patients with elevated levels of VEGF in the serum showed more frequently: GC genotype (P = 0.04), C allele (P = 0.02) at the locus +405 and TT genotype (P = 0.03) at the locus −460. Conclusion Our results strongly support the role of VEGF gene polymorphism in the pathogenesis of psoriasis.